Hair transplantation in mice: Challenges and solutions. Issue 4 (8th June 2016) - Asgari, Azar Z; Rufaut, Nicholas. W.; Morrison, Wayne A.; Dilley, Rodney. J.; Knudsen, Russle; Jones, Leslie N.; Sinclair, Rodney. D.
Abstract: Hair follicle cells contribute to wound healing, skin circulation, and skin diseases including skin cancer, and hair transplantation is a useful technique to study the participation of hair follicle cells in skin homeostasis and wound healing. Although hair follicle transplantation is a well‐established human hair‐restoration procedure, follicular transplantation techniques in animals have a number of shortcomings and have not been well described or optimized. To facilitate the study of follicular stem and progenitor cells and their interaction with surrounding skin, we have established a new murine transplantation model, similar to follicular unit transplantation in humans. Vibrissae from GFP transgenic mice were harvested, flip‐side microdissected, and implanted individually into needle hole incisions in the back skin of immune‐deficient nude mice. Grafts were evaluated histologically and the growth of transplanted vibrissae was observed. Transplanted follicles cycled spontaneously and newly formed hair shafts emerged from the skin after 2 weeks. Ninety percent of grafted vibrissae produced a hair shaft at 6 weeks. After pluck‐induced follicle cycling, growth rates were equivalent to ungrafted vibrissae. Transplanted vibrissae with GFP‐positive cells were easily identified in histological sections. We established a follicular vibrissa transplantation method that recapitulates human follicular unit transplantation. This method has several advantages over current protocols for animal hair transplantation. The method requires no suturing and minimizes the damage to donor follicles and recipient skin. Vibrissae are easier to microdissect and transplant than pelage follicles and, once transplanted, are readily distinguished from host pelage hair. This facilitates measurement of hair growth. Flip‐side hair follicle microdissection precisely separates donor follicular tissue from interfollicular tissue and donor cells remain confined to hair follicles. This makes it possible to differentiate migration of hair follicle cells from interfollicular epidermis in lineage tracing wound experiments using genetically labeled donor follicles.